How Justice Rand Devised His Famous Formula and Forever Changed the Landscape of Canadian Labour Law - Kaplan, William (University of New Brunswick Law Journal, 2011)
Discusses the history of the "Rand Formula," which established the compulsory union dues checkoff for collective work places. A cornerstone of Canadian labour law, the Formula originated in 1946 from an arbitration ruling by Supreme Court Justice Ivan C. Rand following a strike at the Ford motor plant in Windsor, Ontario, in 1945. The political and legal aspects of Rand's ruling are analyzed.